1974
DOI: 10.1002/jss.400020507
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of the lipid phase of membranes from cultured animal cells

Abstract: ESR analysis of membranes from cultured animal cells reveals a more complex lipid phase behavior than that displayed by ideal binary lipid systems. When endoplasmic reticulum membranes from LM cells are spin labeled with a nitroxide derivative of decane, 5N10, and scanned by ESR at 1°C-intervals, the partitioning of 5N10 between the hydrocarbon and aqueous portions of the memb5ane suspension undergoes thermotropic changes at characteristic temperatures of 9 , 16", 22", 32", and 38°C. Lipids extracted from thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

1974
1974
1980
1980

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
1
11
1
Order By: Relevance
“…Keirns On the basis of the best agreement with the aggregate of physical and physiological data, we favor model 1, in which the characteristic temperatures are 220 and 380 for the inner monolayer and 14°and 32°for the outer monolayer of the membranous envelope of NDV. Similar characteristic temperatures (420) can be assigned to the inner and outer monolayers of the LM cell surface membrane, and this very same model best fits the ESR data for LM cell endoplasmic reticulum (21). This physical asymmetry has a compositional precedent in human erythrocyte membranes, where the bulk of the choline containing phosphatides is apparently localized on the outer monolayer, and phosphatidylserine and phosphatidylethanolamine are on the inner monolayer (35,36).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Keirns On the basis of the best agreement with the aggregate of physical and physiological data, we favor model 1, in which the characteristic temperatures are 220 and 380 for the inner monolayer and 14°and 32°for the outer monolayer of the membranous envelope of NDV. Similar characteristic temperatures (420) can be assigned to the inner and outer monolayers of the LM cell surface membrane, and this very same model best fits the ESR data for LM cell endoplasmic reticulum (21). This physical asymmetry has a compositional precedent in human erythrocyte membranes, where the bulk of the choline containing phosphatides is apparently localized on the outer monolayer, and phosphatidylserine and phosphatidylethanolamine are on the inner monolayer (35,36).…”
Section: Discussionsupporting
confidence: 63%
“…Cytoplasmic membranes were isolated from mouse LM cells maintained as monolayer cultures in Eagle's minimal essential medium (MEM) l)lus 0.5%lpel)tone (19). Membranes were isolated as described by Schimmel et al (20) with minor modification (21 Bligh and Dyer (23). The lipid extract (0.4 ml) was filtered through Na2SO4 and glass wool, dried under a stream of nitrogen gas, and suspended in 80 Al of chloroform: methanol (2: 1).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to fluorescent probe analysis the techniques used include differential scanning calorimetry (44), X-ray diffraction (45), electron spin resonance (46)(47)(48), niuclear magnetic resonance (49,50), and the temperature dependence of various enzyme and transport functions (43,51). Evidence for phase transitions in mammalian membranes, however, has been limited to mouse LH cells cultured in monolayers (52,53) and studied by electron spin resonance and the nitroxide spin label, SN10, in association with a numiber of physiological parameters. The present study provides the first clear demonstration of a phase transition in plasma membranes isolated directly from a normal mammalian tissue.…”
Section: (3)mentioning
confidence: 99%
“…The present study provides the first clear demonstration of a phase transition in plasma membranes isolated directly from a normal mammalian tissue. While the mean transition temperature of approximately 26°C is sufficiently below 37°C to preclude a physiological role for the change in state, the transition phenomenon should prove useful in further studies of membrane transport and enzyme reactions as it has in other cell types (43,52,53).…”
Section: (3)mentioning
confidence: 99%
“…Recent evidence suggests that the asymmetric distribution of lipids and proteins across the bilayer membrane of animal cells may result in a physically asymmetric bilayer (8). In accordance with this model, it has been shown that the inner and outer monolayers of the membrane bilayer display two nonidentical sets of characteristic temperatures (9)(10)(11).…”
mentioning
confidence: 73%